2019
DOI: 10.3389/fonc.2019.00277
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib Treatment of Pleomorphic Xanthoastrocytoma in a Child With Down Syndrome

Abstract: Brain tumors are the most common solid neoplasms of childhood, but they are very rarely reported in children with Down Syndrome (DS), who develop more commonly different types of malignancies. In particular, we hereby report the case of an 8-years-old child with DS that presented to our attention for neurological and endocrinological issues. Brain imaging revealed the presence of a mass that was partially resected revealing a histological diagnosis of Pleomorphic Xanthoastrocytoma (PXA), a rare WHO grade II tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A literature review identified reports of PXA concurrent with congenital diseases including Sturge-Weber syndrome, [56] constitutional 22q11.2 deletion syndrome, [57] Familial melanoma-astrocytoma syndrome, [58] and Down syndrome. [59] Interestingly, as one of the most common mutations found in PXAs, BRAF V600E mutation has also been reported to be associated with neurocutaneous melanosis, [48] which could imply an underlying indirect link between PXA and DWM in our case.…”
Section: Discussion and Literature Reviewmentioning
confidence: 81%
“…A literature review identified reports of PXA concurrent with congenital diseases including Sturge-Weber syndrome, [56] constitutional 22q11.2 deletion syndrome, [57] Familial melanoma-astrocytoma syndrome, [58] and Down syndrome. [59] Interestingly, as one of the most common mutations found in PXAs, BRAF V600E mutation has also been reported to be associated with neurocutaneous melanosis, [48] which could imply an underlying indirect link between PXA and DWM in our case.…”
Section: Discussion and Literature Reviewmentioning
confidence: 81%
“…Notably, approximately 70% of patients with PXA exhibit the BRAF V600E mutation 24 , 25 . Moreover, reports of radiological and clinical responses when BRAF inhibitors, such as vemurafenib and dabrafenib, are used as monotherapy or in combination with mitogen-activated protein kinase inhibitors (such as trametinib) have been documented 26 – 29 . Our study included 9 cases subjected to genetic analysis, with 7 individuals (77.8%) exhibiting the BRAF V600E mutation, and 4 (44.4%) presenting with CDKN2A/B homozygous deletion.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of vemurafenib in the nephrotoxicity mouse model studied by Bai et al ( 47 ) was higher (20 mg/kg, twice a day) than our virus studies (10 mg/kg, once a day), which may suggest that low dosages, which are sufficient for virus clearance, would not cause nephrotoxicity. Vemurafenib has also been successfully used with child cancer patients ( 48 – 51 ). It has to be kept in mind, though, that during treatment of life-threatening cancer, manageable toxicity is allowed, whereas more consideration of toxicity has to be taken during treatment of viral infections.…”
Section: Discussionmentioning
confidence: 99%